Maternal characteristics as predictors of immunization status of under-five in Ebonyi State of Nigeria. A community based cross-sectional study - Afoke, Eunice N.; Omaka-Amari, Lois N.; Nwafor, Jude N.; Ochiaka, Raphael E.; Aleke, Christian O.; Okereke, Michael O.; Sylvester, Edu Theresa; Edet, Bassey Rita; Ikechukwu, Ilo Cajetan (Journal of Maternal and Child Health, 2022)
Background: : Childhood immunization with the interacting factors has been a significant public health challenge especially in the sub-Saharan Africa. Nigeria has been presented as one the countries with the worst under-five mortality rates, and factors affecting childhood immunization are poorly understood. This study determined the influence of maternal characteristics as a predictor of immunization status of under-five in Ebonyi State of Nigeria. Subjects and Method: The design in this study is cross-sectional survey. The population of the study was 572,955 under-five children in Ebonyi State from which 2865 was sampled. Data were analyzed using percentages and chi-square. Results: The results revealed that 83.01% of under-5 children were fully immunized, suggesting a high immunization status in Ebonyi State. The chi-square analysis shows a significant influence of mothers’ age (p < 0.05), mothers’ location of residence (p < 0.05), mothers’ educational level (p < 0.05) and immunization status of under-five children. Conclusion: It was concluded that immunization status of under-five children in Ebonyi State was high and maternal characteristics had significant influence on immunization status of under-five children. Thus, it was recommended among others, that government at all levels should provide tangible incentives to mothers who fully immunized their children and promulgate a law to prevent children without immunization cards, also compel mothers, teachers to show full immunization of under-five children by registering in public and private primary schools.